Genome-wide characterization and expression profiling of the TGA gene family in sweet orange (Citrus sinensis) reveal CsTGA7 responses to multiple phytohormones and abiotic stresses - Wang, Min; Ma, Yue; Qiu, Yu-Xin; Long, Si-Si; Dai, Wen-Shan (Frontiers in Plant Science, 2025)
Citrus is widely recognized as one of the most economically important fruit crops worldwide. However, citrus growth is frequently hindered by external environmental stresses, which severely limit its development and yield. The TGA (TGACG motif-binding factor) transcription factors (TFs) are members of the bZIP family and play essential roles in plant defense responses and organ development. Nevertheless, the systematic identification and functional analysis of the TGA family in citrus remains unreported. In this study, genome-wide analysis identified a total of seven CsTGA TFs in Citrus sinensis, which were classified into five subgroups. Phylogenetic and syntenic analysis revealed that the CsTGA genes are highly conserved, with no tandem or segmental duplication events among family members. Promoter sequence analysis identified numerous cis-acting elements associated with transcriptional regulation, phytohormone response, and environmental adaptation in the promoters of CsTGA genes. The expression patterns under five phytohormones and three abiotic stresses demonstrated significant responses of multiple CsTGA genes under various forms of adversity. Among all tested treatments, CsTGA7 showed the most robust response to multiple stresses. Tissue-specific expression pattern analysis revealed potential functional biases among CsTGA genes. In-depth analysis showed that CsTGA7 localized in the nucleus and possessed transcriptional activation activity, consistent with the typical characteristic of transcriptional regulators. In summary, our research systematically investigated the genomic signature of the TGA family in C. sinensis and unearthed CsTGA7 with potential functions in phytohormone signaling transduction and abiotic stress responses. Our study establishes a basis for further exploration of the function of CsTGA genes under abiotic stress.